Francophonie and economic mediation between Asia and Africa: what powers? - (:unkn) unknown (My University, 2018)
The Francophonie can play a key role in structuring the economic dynamics between Asia and Africa. To do this, it can draw on its political achievements and the diversity of its economic space. However, its economic commitment will have to overcome many obstacles related to the respective situations of Africa, Asia and Francophonie itself. At the same time, the Francophonie will have to legitimate its economic action in order not to suffer the performance of the other cooperative spaces that already play the economic mediation between Africa and Asia.
Keywords: African Research